The development of active types of tourism in Kazakhstan: theoretical aspect and practical guidelines* - Mamrayeva, D.G. (BUKETOV BUSINESS REVIEW, 2018)
Tourism is a complex socio-economic process, and its organization requires a serious scientific justification. Studies of the essence of active tourism, its specific features are complex, systematic and territorial. The study of the efficiency of using the tourist and recreational potential of the territory for many regions of Kazakhstan can be an important step on the way to optimizing the regional structure of nature management. At the same time, the development of regional tourism can solve the problem of organizing recreation of the population, attracting foreign tourists to the regions of Kazakhstan, providing them with unique, competitive tourist products with a good bundle of their services. In the article the author developed a classification of active and adventure tourism, systematized data on the territorial organization of active routes, existing and proposed by tourist companies in the regions of Kazakhstan, and also the current state of sport and active tourism in the country was analyzed.